2021
DOI: 10.3389/fnut.2021.675267
|View full text |Cite
|
Sign up to set email alerts
|

Grape Polyphenols Attenuate Diet-Induced Obesity and Hepatic Steatosis in Mice in Association With Reduced Butyrate and Increased Markers of Intestinal Carbohydrate Oxidation

Abstract: A Western Diet (WD) low in fiber but high in fats and sugars contributes to obesity and non-alcoholic fatty liver disease (NAFLD). Supplementation with grape polyphenols (GPs) rich in B-type proanthocyanidins (PACs) can attenuate symptoms of cardiometabolic disease and alter the gut microbiota and its metabolites. We hypothesized that GP-mediated metabolic improvements would correlate with altered microbial metabolites such as short chain fatty acids (SCFAs). To more closely mimic a WD, C57BL/6J male mice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 73 publications
3
19
0
Order By: Relevance
“…In view of this, attention is being focused on finding strategies to promote a healthier environment in the colonic ecosystem, in order to restore a balanced control over the immune-metabolic axis ( Cires et al, 2019 ; Mezhibovsky et al, 2021 ). While pharmacological strategies have resulted mostly ineffective to this aim, several studies have reported the efficacy of polyphenol-rich diets for promoting a healthy gut environment.…”
Section: Introductionmentioning
confidence: 99%
“…In view of this, attention is being focused on finding strategies to promote a healthier environment in the colonic ecosystem, in order to restore a balanced control over the immune-metabolic axis ( Cires et al, 2019 ; Mezhibovsky et al, 2021 ). While pharmacological strategies have resulted mostly ineffective to this aim, several studies have reported the efficacy of polyphenol-rich diets for promoting a healthy gut environment.…”
Section: Introductionmentioning
confidence: 99%
“…Uterus and liver were weighed. Ileum and colon segments were dissected as previously described ( Tveter et al, 2020 ; Mezhibovsky et al, 2021 ) and then flushed with ice-cold, sterile PBS (pH 7.4) to collect luminal contents for targeted metabolomics. Samples were placed in cryogenic tubes, snap frozen in liquid nitrogen, and stored at −80°C until analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Body composition was measured using an EchoMRI body composition analyzer (EMR-129, Echo Medical Systems, Houston, TX) at 0, 4, 7, 10, 14, and 18 weeks post-treatment. After 9 weeks of treatment, an oral glucose tolerance test was performed as previously described ( Tveter et al, 2020 ; Mezhibovsky et al, 2021 ). During the 9th and 10th week post-treatment, indirect calorimetry was performed on 9 mice per group using a Comprehensive Laboratory Animal Monitoring System with temperature and light control enclosure (CLAMS, Columbus Instruments, Columbus, Ohio) as previously described ( Mezhibovsky et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supplementation with grape polyphenols reduced Western diet (WD)-induced adiposity and hepatic steatosis in mice by increasing the abundance of Akkermansia muciniphila and butyrate and sugar expenditure in the distal intestine [ 50 ].…”
Section: Gut Microbiota-derived Metabolites In the Pathogenesis Nafld And Nashmentioning
confidence: 99%